Investigation of granite rocks radiation-chemical durability - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedeva, E.P.; Sayenko, S.Yu.; Tarasov, R.V.; Uvarov, V.L.; Kholomeyev, G.A.; Shevyakova, E.P.; Fedorets, I.D. (Вопросы атомной науки и техники, 2002)
Gamma-activation analysis is used to study dynamics of leaching of various elements from granite samples. The sample preliminary irradiation and activation was carried out in the field of bremsstrahlung of electron accelerator. With the use of Ge(li) detector concentration of sodium, cesium and manganese isotopes in the leachant as well as the dependence of diffusion coefficient are determined.